Developing Flipped Classroom-based Mobile Learning Media to Teach Optical Physics - Setya Fery Widyastuti; Endro Dwi Wuryanto (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
The application of flipped classrooms-based M-learning media will make learning more planned and systematic. Therefore, students will be more enthusiastic and independent in the learning process. The study aims to design a flipped classrooms-based mobile learning media to teach optical physics and investigate its validity, effectiveness, and practicality. This study employed a research and development method, including defining, designing, developing, and disseminating. Participants in this research were 25 students. Research instruments included expert validation sheets towards learning media developed, a test evaluation of learning results, student response questionnaires, and student activity observation sheets. The expert validation results were analyzed quantitatively and then interpreted to determine the learning media's feasibility. The test and questionnaire results were analyzed in descriptive statistics, while the observation data were analyzed qualitatively. The results reveal that the application of flipped classroom-based M-learning media in the Optical Physics course is categorized as valid, effective, and practical. Furthermore, the application has a significant effect on student achievements, with a significant difference between the pre-test and post-test. Finally, most students showed positive responses to the application.